Science in Places of Grandeur: Communication and Engagement in National Parks. (29th May 2018) - Watkins, Tim; Miller-Rushing, Abraham J; Nelson, Sarah J
Abstract: The USA has set aside over 400 national parks and other protected areas to be managed by the National Park Service (NPS). Collectively, these sites attract over 300 million visits per year which makes the NPS one of the largest informal education institutions in the country. Because the NPS supports and facilitates scientific studies in parks, the national park system provides abundant opportunity for biologists and other scientists to engage global audiences in learning, exploring, and even conducting science. Those opportunities are best pursued through collaborations among scientists and the professional communication staff (interpreters, educators, media specialists, etc.) of parks and their partner organizations. This article describes unique opportunities and rationale for such collaborations, presents several examples that highlight the range of activities and lessons drawn from them, and invites scientists to conduct studies in parks and bring their science into the public eye.